Combined toxicity assessment of myclobutanil and thiamethoxam to zebrafish embryos employing multi-endpoints. (15th January 2021) - Shen, Weifeng; Yang, Guiling; Guo, Qi; Lv, Lu; Liu, Li; Wang, Xinquan; Lou, Bao; Wang, Qiang; Wang, Yanhua
Abstract: It is necessary to understand the interactions between different pesticides in ecotoxicology because pesticides never appear as individual compounds but rather in combinations with other compounds. In this study, we planned to explicate the combined toxic effect of myclobutanil (MYC) and thiamethoxam (THI) on the zebrafish ( Danio rerio ) by adopting multiple biomarkers. Results unraveled that the 96-h LC50 values of MYC to D. rerio at various life phases ranged from 5.2 to 10.3 mg L −1, which were lower than those of THI ranging from 147 to 246 mg L −1 . Combinations of MYC and THI exhibited synergetic toxicity to zebrafish embryos. The activities of antioxidative enzymes (T-SOD, Cu/Zn-SOD and POD) and detoxification enzyme (GST) were obviously varied in most of the MYC, THI and combined exposures compared to the control. The mRNA expressions of eight genes ( Cu-sod, cas3, il-8, cxcl, erα, crh, cyp17 and dio1 ) involved in antioxidation, apoptosis, immunity and endocrine were obviously altered in the combined exposure of MYC and THI compared to their individual exposures. Our findings hinted the threats when YMC and THI co-existed, which would be beneficial for the risk assessments of pesticide mixtures. Graphical abstract: Image 1 Highlights: Myclobutanil exhibited higher toxicity to zebrafish than thiamethoxam. Mixtures of myclobutanil and thiamethoxam exerted synergistic effect on zebrafish. Expressions of 8 genes in mixtures elicited greater variations than individuals. Synergistic responses should be incorporated into risk evaluation of pesticide. Abstract : Combined toxicity and potential mechanism of myclobutanil and thiamethoxam to the zebrafish.